Analysis of mycobacterial infection-induced changes to host lipid metabolism in a zebrafish infection model reveals a conserved role for LDLR in infection susceptibility. Issue 83 (December 2018) - Johansen, Matt D.; Hortle, Elinor; Kasparian, Joshua A.; Romero, Alejandro; Novoa, Beatriz; Figueras, Antonio; Britton, Warwick J.; de Silva, Kumudika; Purdie, Auriol C.; Oehlers, Stefan H.
Abstract: Changes to lipid metabolism are well-characterised consequences of human tuberculosis infection but their functional relevance are not clearly elucidated in these or other host-mycobacterial systems. The zebrafish- Mycobacterium marinum infection model is used extensively to model many aspects of human- M. tuberculosis pathogenesis but has not been widely used to study the role of infection-induced lipid metabolism. We find mammalian mycobacterial infection-induced alterations in host Low Density Lipoprotein metabolism are conserved in the zebrafish model of mycobacterial pathogenesis. Depletion of LDLR, a key lipid metabolism node, decreased M. marinum burden, and corrected infection-induced altered lipid metabolism resulting in decreased LDL and reduced the rate of macrophage transformation into foam cells. Our results demonstrate a conserved role for infection-induced alterations to host lipid metabolism, and specifically the LDL-LDLR axis, across host-mycobacterial species pairings. Highlights: LDL is dysregulated in zeEbrafish embryos infected with Mycobacterium marinum. Knockdown of LDLR expression lowers infection burden and normalises infection-induced changes to lipid metabolism. Mycobacterial infection-induced changes in lipid metabolism are highly conserved between host and pathogen species pairings.